2005
DOI: 10.1038/oby.2005.71
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Behavioral Aspects of Bariatric Surgery

Abstract: 2 ) or those with less severe obesity accompanied by significant comorbidities. Sustained postoperative weight loss and improvements in obesity-related health problems make bariatric surgery the most effective treatment for this population. Nevertheless, most experts agree that psychosocial and behavioral factors contribute to successful postoperative outcomes. This paper reviews the literature on the preoperative psychosocial status, eating behaviors, and quality of life of patients who seek bariatric surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
262
2
26

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(302 citation statements)
references
References 115 publications
(211 reference statements)
12
262
2
26
Order By: Relevance
“…However, depressive and anxiety symptoms, as correlates of psychological stress with regard to obesity, seemed to be predictive of weight loss after surgery. Both psychosocial and behavioral factors contribute to the successful post-operative outcomes (Sarwer et al, 2005). Another positive impact of surgery may be the improvement in socio-economic level of obese people after weight loss (Hawke et al, 1990, Naslund andAgren, 1991;Herpetz et al, 2003), but this parameter, as well as depression scores were not recorded in our study.…”
Section: Discussionmentioning
confidence: 59%
“…However, depressive and anxiety symptoms, as correlates of psychological stress with regard to obesity, seemed to be predictive of weight loss after surgery. Both psychosocial and behavioral factors contribute to the successful post-operative outcomes (Sarwer et al, 2005). Another positive impact of surgery may be the improvement in socio-economic level of obese people after weight loss (Hawke et al, 1990, Naslund andAgren, 1991;Herpetz et al, 2003), but this parameter, as well as depression scores were not recorded in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Previous research has demonstrated that the prevalence of psychiatric comorbidity is increased in bariatric surgery patients and mood disorders appear to be the most common condition. 8 The relationship between obesity and depression is complex and the causal pathway may be bidirectional or reciprocal. Studies of adolescents suggest that depression during adolescence may precede obesity in young adulthood and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Weight reduction in the severely obese is accompanied by improvements in HRQL and some studies indicate that a dose-response relationship exists between the magnitude of weight loss and HRQL benefits. [2][3][5][6][7][8] However, severe obesity is a refractory condition that is extremely difficult to master in the long run and conventional treatment, including various diet regimens, lifestyle modification programs and pharmaceutical agents, is relatively ineffective in the long-term perspective. 1 At present, surgical intervention is the only treatment alternative yielding more enduring weight loss and improvements in health status and HRQL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remodelling together made it easier to strengthen the interrelationships within the family, also facilitating attaining unity and the maintenance of lifestyle modifications. According to research, individuals often experience a positive change in their relationships after undergoing weight loss surgery (Clark et al, 2014; Sarwer, Wadden, & Fabricatore, 2005). Wedin et al (2014) have reported that being married was 7.1 odd ratio with sustained weight loss.…”
Section: Discussionmentioning
confidence: 99%